Interleukin-8 and -17 levels in the sera of vaccinated subjects receiving a booster dose of measles virus: A follow-up study in Iraq - Laith A I K Al-Kaif; Younis A K Al-Khafaji; Sarah K Shandaway; Uday H K AL-Janabi; Kawther Jawad Kadhim; Mohammed Ahmed Akkaif (Medical Journal of Babylon, 2023)
Background: Measles is a highly contagious viral infection that can lead to severe complications. Vaccination has successfully reduced measles cases; however, the immune response to booster doses of the measles vaccine is not fully understood. This follow-up study aimed to investigate the levels of interleukin-8 (IL-8) and IL-17 in the sera of vaccinated subjects after receiving a booster dose of the measles virus. Objectives: This follow-up study evaluated the levels of IL-8 and IL-17 in the sera of volunteers who received a second booster dose of the measles virus vaccine compared to a control group. Materials and Methods: Forty volunteers were included in the study, with 20 volunteers receiving a second booster dose of the vaccine and the remaining volunteers serving as the control group. The levels of IL-8 and IL-17 were measured using the enzyme-linked immunosorbent assay at various time intervals. Results: The results revealed significant differences in IL-8 levels, whereas IL-17 levels showed non-significant differences among the tested subjects at different time intervals (P ≤ 0.05). In the vaccinated group, the mean IL-8 level after one week was 192.04 ± 31.44 pg/mL, whereas it decreased to 30.89 ± 4.44 pg/mL after 7 weeks, showing a significant difference between these two periods. The control group had an IL-8 level of 367.95 ± 32.61 pg/mL. Regarding IL-17, there was no significant difference between the 3-week measurement (415.63 ± 61.12 pg/mL) and the 7-week measurement (848.61 ± 54.29 pg/mL) in the vaccinated group, as well as the control group (819.46 ± 75.33 pg/mL). Conclusions: The findings of this study suggest that the levels of IL-8 decreased, whereas there was variation in IL-17 levels after administering a second booster dose of the measles vaccine compared to normal subjects. These results contribute to our understanding of the immune response following a booster dose of the measles vaccine and highlight potential differences in the immune profile of vaccinated individuals compared to the control group.